Study on Selective Credit Control in India: The impact of credit control on economic stability and development in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Credit control is an important tool used by the Reserve Bank of India, a major monetary policy instrument used to control the economy's demand and supply of cash (liquidity). Control over the credit that commercial banks offer is controlled by the Central Bank. The RBI is using such a strategy to bring Economic Development with Stability This means that banks can not only monitor inflationary economic patterns, but also boost economic growth, eventually leading to a rise in the stability of real national income. Given its functions, such as issuing notes and retaining cash reserves, credit not regulated by the RBI will lead to social and economic instability in the country. To foster financial stability and economic growth, the banking system is regulated. While growing public sector ownership of banks and a combination of joint-stock firms, branches, cooperatives and corporations has been observed in the post-independence period, it does not guarantee the optimal banking structure that financial reforms have sought since 1991. An significant area in the study of macroeconomics is the banking system and money management. Since the monetary policies of the Government and the RBI will influence our defence budget in several ways, we should be fully aware of this important area of the macroeconomic system as defence planners.